Utilizing mHealth methods to identify patterns of high risk illicit drug use. (1st June 2015) - Linas, Beth S.; Latkin, Carl; Genz, Andrew; Westergaard, Ryan P.; Chang, Larry W.; Bollinger, Robert C.; Kirk, Gregory D.
Highlights: Ecological Momentary Assessment (EMA) data modeled using latent class growth mixture models. Low, medium and high intensity drug using groups had distinct behavioral profiles. High intensity drug users had reduced odds of attending outpatient appointments. High intensity drug users were less likely to be medically insured. EMA captured non-uniformity of drug use and users at risk for poor healthcare access and utilization. Abstract: Introduction: We assessed patterns of illicit drug use using mobile health (mHealth) methods and subsequent health care indicators among drug users in Baltimore, MD. Methods: Participants of the EXposure Assessment in Current Time (EXACT) study were provided a mobile device for assessment of their daily drug use (heroin, cocaine or both), mood and social context for 30 days from November 2008 through May 2013. Real-time, self-reported drug use events were summed for individuals by day. Drug use risk was assessed through growth mixture modeling. Latent class regression examined the association of mHealth-defined risk groups with indicators of healthcare access and utilization. Results: 109 participants were a median of 48.5 years old, 90% African American, 52% male and 59% HIV-infected. Growth mixture modeling identified three distinct classes: low intensity drug use (25%), moderate intensity drug use (65%) and high intensity drug use (10%). Compared to low intensity drug users, high intensity users were younger, injected greater than once per day, and shared needles. At the subsequent study visit, high intensity drug users were nine times less likely to be medically insured (adjusted OR: 0.10, 95%CI: 0.01–0.88) and at greater risk for failing to attend any outpatient appointments (aOR: 0.13, 95%CI: 0.02–0.85) relative to low intensity drug users. Conclusions: Real-time assessment of drug use and novel methods of describing sub-classes of drug users uncovered individuals with higher-risk behavior who were poorly utilizing healthcare services. mHealth holds promise for identifying individuals engaging in high-risk behaviors and delivering real-time interventions to improve care outcomes.